Preliminary study on the energetic Potential of Palm cuesco and coconut shellin colombia - Forero Núñez, Carlos; Cediel Ulloa, Alexandra; Rivera Gil, José L.; Suaza Montalvo, Andrea; Sierra Vargas, Fabio E (Ingeniería Solidaria, 2012)
The use of agro-industrial waste in the energy industry has developed in recent years due to its application solving two different problems: the treatment of solid residues and the reduction of greenhouse gases.In Colombia there are many agroindustry residues; among them are coconut shells (the part that protects the white pulp) and the cuesco (shell of the fruit) of the African oil palm, both of which can be used forenergy production. The authors present a bibliographical review through which it is possible to determine the energetic potential of these residues. This is the first stage of a project undertaken in 2011 by the research group “Mechanisms for clean development and energy management” of the faculty of Engineering of the Universidad Nacional de Colombia, that seeks to produce electricity through fixed bed gasification ofsaid waste.
Keywords: coconut shell; cuesco; power generation; energetic potential; agro-industrial waste